ChemInform Abstract: Palladium‐Catalyzed Aerobic Aminooxygenation of Alkenes for Preparation of Isoindolinones. Issue 15 (24th March 2016) - Kou, Xuezhen; Li, Yu; Wu, Liang; Zhang, Xinghua; Yang, Guoqiang; Zhang, Wanbin
Abstract: A series of functionalized alkenes is treated with excess carboxylic acid including amino acids (X) in the presence of molecular oxygen under conditions A) (oxidation mechanism).